A nation awakened out of its sleep paralysis: A review of Pumla Dineo Gqola's Rape: A South African Nightmare. Issue 2 (2nd April 2016) - Zikalala, Zukolwenkosi
Abstract: A haunting reality in post-1994 South Africa is the high statistics and incidences of rape. Pumla Dineo Gqola takes on this tough subject in her latest book Rape: A South African Nightmare, a subject which unfortunately, when talked about on public forums and in gender talk, becomes a series of miscommunications and false conversations. The following review is mindful of how the dense intellectual thought and material which Gqola engages in her third book is elucidated for a broader audience. It is a contribution towards South Africa's public discussion of rape. The task of unpacking rape myths, and the perpetuation of rape culture, is achieved by Gqola in her analysis of various high-profile and highly publicised rape cases. I highlight the various ways in which a very deliberate feminist ethic and activist commitment informs the entire book. This review, whilst mostly being an appreciation of the book, refuses – as Gqola herself does – to pretend that South Africans are going to be 'shocked' by this book as though hearing about rape for the first time. This proceeds from reading several incidences Gqola examines in the way that she does: sensitive about not recreating the trauma of rape, yet clearly going to the core and unpacking the logics and language that make rape culture.